2001
DOI: 10.1046/j.1471-8278.2001.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation (with enrichment) and characterization of trinucleotide microsatellites from Phlebotomus perniciosus, a vector of Leishmania infantum

Abstract: Mitochondrial DNA characterization of the sandfly Phlebotomus perniciosus has not resolved the population structure of its Iberian lineage. For this purpose, four AGC-and seven AGG-class microsatellite loci were characterized, after their isolation using Biotin-Avidin enrichment and the screening of plasmid libraries by polymerase chain reaction. Of the five polymorphic loci analysed in four Spanish populations, four showed patterns of allele diversity consistent with migration from a southern Ice Age refuge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Locus-specific primers were designed based on the sequences flanking the microsatellites, and PCR conditions were established for four of the five loci used in the present studyAAm13, AAm20 and AAm82 with AGG-class repeats and AAm24 with AGC-class repeats (Aransay et al, 2001). A new AGC-class locus is reported here for the first time.…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Locus-specific primers were designed based on the sequences flanking the microsatellites, and PCR conditions were established for four of the five loci used in the present studyAAm13, AAm20 and AAm82 with AGG-class repeats and AAm24 with AGC-class repeats (Aransay et al, 2001). A new AGC-class locus is reported here for the first time.…”
Section: Dna Extractionmentioning
confidence: 99%
“…We report here the use of polymorphic microsatellite DNA loci, isolated by Aransay et al (2001), to investigate the population structure of P. perniciosus in Spain. Such studies of insect transmitters of disease are potentially important for planning intervention strategies, as they can help predict the dispersal not only of vectorial traits associated with specific populations but also of genetically modified organisms and the genes they carry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nine of the 11 loci observed heterozygosity was lower than expected heterozygosity, which is not surprising given that we tested these microsatellites on several isolated laboratory populations. The dinucleotide loci described here are more polymorphic than other published sandfly microsatellite loci; for example, observed heterozygosity at two trinucleotide microsatellites in wild-caught Lutzomyia whitmani was 0.33 and 0.55 (Day & Ready 1999), whilst populations of Phlebotomus perniciosus from Spain possessed 3 -5 alleles and had observed heterozygosity values between 0.025 and 0.367 at five trinucleotide loci (Aransay et al 2001). Given that inbreeding is expected to be prevalent in small laboratory populations, the variability observed at these loci was somewhat unexpected.…”
mentioning
confidence: 61%
“…However, this seems unlikely for three main reasons. First, several studies using the same protocol (Hammond et al, 1998) have been successfully done (examples can be found in: Aransay et al, 2001;Bailey et al, 2005;Berendonk and Evans, 2004;Berendonk and Dobson, 2006;Burland et al, 2001;Horning et al, 2003;Liu et al, 2005;Liu et al, 2006;Pai et al, 2003;Tero and Schlotterer, 2005;Harper et al, 2006); Second, our laboratory is experienced in the development of microsatellites in different group of organisms, including birds (Jeffery et al, 2001), reptiles ; mammals (Radespiel et al, 2001), insects (Wilcock et al, 2001;Seabra et al, 2002;Williams et al, 2002) and earthworms (Harper et al, 2006); and third, the few reports on microsatellite isolation in this group of birds (only one record for Sterna; Szczys et al, 2005 and two for seagulls; Given et al, 2002;Tirard et al, 2002) and several personal communications from researchers that were not successful in the development of polymorphic loci in tern species.…”
Section: Molecular Markers In Terns 683mentioning
confidence: 99%